Sustainable and Precarious Employment in the Russian Federation - V. N. Bobkov; E. V. Odintsova; G. L. Podvoisky (Мир новой экономики, 2023)
The subject of the present study is the relationship between sustainable and precarious employment and their scale in the Russian economy. The topic of the article is “Sustainable and precarious employment in the Russian Federation”. The aim of the study is to consider the characteristics of sustainable and precarious employment through the prism of the extended and traditional concepts of the labour force and to determine their scale in the whole of the Russian Federation and in individual sectors of employment on the basis of objective indicators of precarious employment substantiated and verified by the authors. The research methodology is based on a qualitative and quantitative analysis and synthesis of the characteristics of sustainable and precarious employment, including consideration of the extended and traditional concepts of the labour force, the classification of modern employment, as well as the verification of its indicators and their variable application. The scope of the research results is to develop consensus methodological approaches to the study of sustainable and precarious employment, as well as their regulation by government authorities. The authors concluded that precarious employment in the Russian Federation is widespread, which reduces the quality of employment and requires legislative and practical restrictions.